Customisable cloud-based IOT monitoring system with smartphone interface - Chew, Xiang Kai (2023)
This project is a mobile application project that related to kids healthy eating. The main purpose is to let kids to recognize the healthy food and not healthy food. Based on above, this project has divided to some module to achieve the main purpose. First will be the Food List module. This module includes several healthy and not healthy food and provide the information short and concise. Not only that, some animation also will be provided to attract the attention of kids. Those animation is related to every food. Through this, kids’ attention will not be distracted and can recognize food and some of the information of food. All the information will be store in Firebase Another module will be AR Camera. This module provides an environment for kids to augment the prepared 3D model to reality, kids can interact with it and recognize the food easier. Kids just need to open the module and find a plane, then can select a food model to place and multiple places for same or different model and geometric transformation such as transformation, scaling and rotation is enabled for kids to interact with. The next modules will be calculating the kid’s healthy status by provide certain information, the system will calculate the healthy status of the kids. This can interact with another module which is some solution for the kids with health problem. In this module, user can know what the solution is when kids are overweight, underweight, and so on. In short, this application is aim to let kids eat healthier by provide more interesting interaction like animation and augmented reality and support by some function to track health status of kids and solve the problem when health problem occur.